Polarization pulling and signal amplification using Raman scattering for Polarization Division Multiplexing transmission system - Perlicki, Krzysztof (Photonics Letters of Poland, 2011)
The numerical modeling of Raman polarization attraction and amplification process in the telecommunication band around 1550nm are presented. The possibility of achieving both polarization pulling and amplification in a Polarization Division Multiplexing transmission system by exploiting the polarization dependence of stimulated Raman scattering is investigated. The acceptable crosstalk and Raman gain for Polarization Division Multiplexing transmission systems were achieved for some attraction/amplification block parameters. Full Text: PDF References: G.P. Agrawal, Fiber-Optic Communications Systems (New York, Wiley 2002). M. Martinelli et al."Evidence of Raman-induced polarization pulling", Opt. Exp. 2, 947 (2009). [CrossRef] A. Galtarossa et al., "Polarized Backward Raman Amplification in Randomly Birefringent Fibers ", J. Lightwave Technol. 11, 4055 (2006). [CrossRef] X. S. Yao et al., "All-optic scheme for automatic polarization division demultiplexing", Opt. Exp. 15, 7407 (2007). [CrossRef] D. van den Borne et al., "PMD-induced transmission penalties in polarization-multiplexed transmission", J. Lightwave Technol. 12, 4004 (2005). [CrossRef] E. Rochat et al., "Polarisation and wavelength division multiplexing at 1.55 ?m for bandwidth enhancement of multimode fibre based access networks", Opt. Exp. 10, 2280 (2004). [CrossRef] E. Collet, Polarized light in fiber optics (Lincroft, NJ, The PolaWave Group 2003). Q. Lin et al., "Statistics of polarization-dependent gain in fiber-based Raman amplifiers", Opt. Lett. 4, 227 (2003). [CrossRef] E. B. Saff et al., "Distributing many points on a sphere", Math. Intell. 1, 5 (1997). [CrossRef]